Intersubjektivitas, Cinta dan Harapan Antara Rintaro dan Waguri dalam Anime The Fragrant Flower Blooms With Dignity Ditinjau dari Filsafat Eksistensialisme Gabriel Marcel - Oktavianus Nong Vicky; Gabriel Angelo Gedi; Ferdinan Selestino Trifon; Molsiprimka Trio D. M. Asiki; Aurelius Mosa (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze intersubjectivity, love, and hope in the anime The Fragrant Flower Blooms With Dignity through the perspective of the existentialist philosophy of Gabriel Marcel. The research employs a qualitative method using a literature review and content analysis approach. Data were collected from relevant philosophical texts on Marcel’s thought and from the analysis of scenes, dialogues, and character development in the anime. The findings reveal that the relationship between Kouruko Waguri and Rintaro Tsumugi reflects the concept of intersubjectivity as an authentic encounter between “I” and “Thou,” where both individuals recognize each other as subjects. The concepts of being and presence are manifested through genuine presence and relational openness, while having functions as a supporting element that does not lead to possessiveness. Furthermore, fidelity, love, and hope emerge as central dimensions in the fulfillment of the characters’ existence, as these aspects enable their relationship to develop in a meaningful and profound way. This study demonstrates that popular cultural works such as anime can serve as relevant media for philosophical reflection in understanding human existence as inherently relational.